STRUKTUR DAN FUNGSI TARI AMAQ ABER DESA MENDANA RAYA KECAMATAN KERUAK KABUPATEN LOMBOK TIMUR - Yuniarni, Ema (TAMUMATRA, 2019)
Amaq Aber dance at the Traditional Sanggar at Mendana Raya Village has a special uniqueness that makes it worth knowing more about its structure and function. This study focused on the structure of the Amaq Aber Dance seen from the motion of the elements of dance and performance function of Amaq Aber.This type of research used a descriptive type of qualitative method. The subject in this study was AmaqAberdancein the Amaq Aber Village of Mendana Raya, Keruak District, and East Lombok Regency. Data collection technique used in this study was interview, observation and documentation. Data analysis techniques used consisted of four stages, namely, data collection (data collection), reduction (data reduction), data display (data presentation), and conclusions drawing / verification (conclusion checker and verification).The results of this study included the Form of AmaqAber Dance which being danced first, called Datu Bajang Dance, consisted of the movement of two dancers as bodyguards and two dancers as rulers. The second part of the dance is called AmaqAkus dance, which was the king's messenger dance with irregular and non-patterned movements. Part three dance is called the Panji Dance, which was a princess, a prince and both bodyguards. Part four dance is called TariPanji as well, but only penguaya dances (princess and prince). The dance function of AmaqAber was as a treatment, repellent and entertainment.